Studies of Vietnamese Pteridophyte Flora 3 - Cheng-Wei Chen; Van Truong Do; Quang Cuong Truong; Viet Dai Dang; Hong Truong Luu; Yi-Shan Chao; Yao-Moan Huang; Kuo-Fang Chung (PhytoKeys)
This is the third paper in a series dedicated to updating the knowledge of the Vietnamese pteridophyte flora. Based on recent collections, we first reported three new national records of ferns: Haplopteris yakushimensis, Lindsaea kohkongensis, and Pteris pseudowulaiensis. Secondly, we conducted phylogenetic analyses to investigate the placements of Lindsaea kohkongensis and Leptochilus poilanei, each based on three plastid DNA markers. Our results revealed that Lindsaea kohkongensis is sister to L. ensifolia, while Leptochilus poilanei is embedded within L. cantoniensis. We discussed these results in the context of systematics. Lastly, we reported chromosome numbers for 20 fern species in Vietnam. For seven of these species, including Gymnosphaera salletii, Lepisorus spicatus, Leptochilus poilanei, Pteridrys costularis, Pteris latipinna, Pyrrosia eberhardtii, and Tectaria setulosa, these counts were recorded for the first time. Additionally, three new cytotypes were identified for Diplazium doederleinii, Pteris esquirolii, and Tectaria harlandii. This study underscores the need for more diverse data, including DNA sequences, chromosome numbers, and reproductive modes, to be collected and integrated into systematic studies and taxonomic treatments to enhance our understanding of Vietnam’s pteridophyte flora.